Analisis Pengendalian Persediaan Pakan Dengan Metode Economic Order Quantity (EOQ) Untuk Meminimalisir Biaya - Deva Ajib; Setyo Adjie; Edi Santoso (Universitas Muhammadiyah Ponorogo, 2018)
This research was carried out with the theme of controlling raw material inventory in Jaya Poultry Farms in Paringan Village, Jenang District, Ponorogo Regency. This study aims to determine the application of the Economic Order Quantity (EOQ) method to reduce the cost of feed supplies and to determine the possibility of increasing the efficiency of corn raw material inventory by the Economic Order Quantity (EOQ) method. This research uses quantitative descriptive methods. The analytical tool used is Economic Order Quantity (EOQ), Frequency of Purchase, Total Inventory Cost (TIC), Safety Stock, Maximum Inventory and Re Order Point. Source of data used in this study are primary data and secondary data. Data collection is done by interview, observation, documentation, and literature study. The results showed that the efficiency of procurement of corn raw material inventories at Jaya Poultry farms could be increased by the Economic Order Quantity (EOQ) method and the use of the Economic Order Quantity (EOQ) method in companies could reduce the cost of corn raw material inventory being cheaper when compared to company policy which has been applied by the company.